Further Studies on the Mechanism for the Antithrombotic Effects of Naroparcil, an Orally Active Thioxyloside Compound - Masson, P.; Theveniau, J.; Coup, D.; Grégoire, T.; Vaillot, M.; Dupouy, D.; Sié, P.; Boneu, B.; Millet, J. (Thrombosis and Haemostasis, 1999)
The antithrombotic β-D-xyloside, naroparcil, has previously been shown to induce a dose-related increase of circulating glycosaminoglycans (GAGs) together with an antithrombin activity (anti-IIa) via heparin cofactor II (HCII) in the rabbit. In order to go further in the mechanisms, the relationship between the antithrombotic activity, the HCII-mediated anti-IIa activity and the plasma GAG content was investigated. We showed that the in vitro specific activity on the inhibition of thrombin by HCII of the plasma GAG extract from naroparcil-treated rabbits was increased by a factor of 60 when compared to controls. In addition, the fractionation of the plasma GAG extract by affinity chromatography on immobilized HCII led to a more potent material whereas the low-affinity fraction was shown to be inactive in thrombin inhibition by HCII.The qualitative analysis of GAGs showed the presence of the ΔDi-4S DS disaccharide, undetectable in control, which accounted for 22% in the unfractionated GAG extract and for 60% in the high affinity fraction. In vitro experiments using immuno-depleted plasma in antithrombin III (ATIII), HCII or both, indicated that the anti-IIa activity of the plasma GAG extract from naroparcil-treated rabbits was mainly due to HCII potentialisation. The unfractionated GAG extract and the high affinity fraction were shown to be antithrombotic in a Wessler-based model in the rat, giving ED80 values of 610 UA/kg and 56 UA/kg respectively whereas the low-affinity fraction was devoid of any antithrombotic activity. These results show that the antithrombotic activity of naroparcil is dependent on modification in the plasma GAG profile which inactivates thrombin via the HCII.